Examining the motives of the deaf watching news programs on TV related to satisfaction level - Kurnia Standi; Asep Suryana; Jimi Narotama Mahameruaji (ProTVF, 2023)
Background: Television is still the media of choice used by various layers of society to seek information; one of the programs in question is news programs. On the other hand, television still relies on audiovisuals to convey its information. This phenomenon becomes an obstacle for deaf people to get the necessary information. Therefore, it encourages KPI with the Ministry of Social Affairs of the Republic of Indonesia to work with sign language interpreters to provide access to deaf people to obtain information. Purpose: This study aims to test the relationship between the motives of Deaf people in watching news programs on television and the level of satisfaction with news programs after the availability of accessibility. These motives include information, personal identity, integration and social interaction, and entertainment motives. The theory used as the basis for this research is the Uses and gratification Theory. Methods: The analysis technique used in this research is descriptive and inferential analysis. The target population in this study were West Java Gerkatin members who watched news programs on television and understood BISINDO or SIBI; with probability sampling, We determined a sample of 95 people. Results: This study shows a significant relationship between the motives of deaf people to watch news programs on television and their level of satisfaction with news programs after accessibility. There is a moderate relationship between information motives and the level of satisfaction with news programs after accessibility. There is a substantial degree of relationship between personal identity motives and the level of satisfaction with news programs after accessibility. There is a moderate level of relationship between integration and social interaction motives with the level of satisfaction with news programs after accessibility, and there is a moderate level of relationship between entertainment motives and the level of satisfaction with news programs after accessibility. Implications: Providing knowledge that sign language interpreters need to be maximized in conveying information so that information can be easily transmitted.